2018
DOI: 10.1371/journal.pone.0190967
|View full text |Cite
|
Sign up to set email alerts
|

Serum galactose-deficient-IgA1 and IgG autoantibodies correlate in patients with IgA nephropathy

Abstract: IgA nephropathy is an autoimmune disease characterized by IgA1-containing glomerular immune deposits. We previously proposed a multi-hit pathogenesis model in which patients with IgA nephropathy have elevated levels of circulatory IgA1 with some O-glycans deficient in galactose (Gd-IgA1, autoantigen). Gd-IgA1 is recognized by anti-glycan IgG and/or IgA autoantibodies, resulting in formation of pathogenic immune complexes. Some of these immune complexes deposit in the kidney, activate mesangial cells, and incit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…The contribution of galactose-deficient IgA1 to IgAN pathogenesis has been validated in many studies. [4][5][6] Moreover, the presence of galactose-deficient IgA1(Gd-IgA1) in the glomerular deposits of patients with IgAN has been proven by immunohistochemical staining using the galactose-deficient IgA1-specific monoclonal antibody KM55, 7,8 which reinforces the important role that galactose-deficient IgA1 plays in IgAN.…”
mentioning
confidence: 79%
“…The contribution of galactose-deficient IgA1 to IgAN pathogenesis has been validated in many studies. [4][5][6] Moreover, the presence of galactose-deficient IgA1(Gd-IgA1) in the glomerular deposits of patients with IgAN has been proven by immunohistochemical staining using the galactose-deficient IgA1-specific monoclonal antibody KM55, 7,8 which reinforces the important role that galactose-deficient IgA1 plays in IgAN.…”
mentioning
confidence: 79%
“…The formation of circulating immune complexes followed by their renal deposition in patients with IgAN is driven by presence of terminal GalNAc on Gal-deficient IgA1 and its recognition by autoantibodies (Novak et al 2015;Knoppova et al 2016). Patients with IgAN have elevated serum levels of IgA1 with terminal GalNAc that correlate with serum levels of IgG autoantibodies (Placzek et al 2018). Initial theories on the origin of this IgA1 glycosylation phenotype proposed that addition of Gal would be impaired due to C1GALT1 reduced expression caused by a COSMC mutation(s).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically, IgAN is characterized by mesangial cell proliferation with IgA-IC deposition in the glomerular mesangium, which is indistinguishable from pathologic findings of HSPN [2,12,14]. Regarding the pathogenesis of IgAN, several studies that investigated aberrant IgA1 O-glycosylation indicated that galactose-deficient IgA1 (Gd-IgA1) plays a pivotal role in the progression of IgAN [15][16][17][18][19][20][21][22][23]. According to these studies, patients with IgAN have aberrant IgA1 molecules with a Gal deficiency of O-linked glycans in the hinge region, which indicates that Gd-IgA1 consists of terminal N-acetyl-galactosamine (GalNAc) or sialylated GalNAc [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%